Erythema nodosum - Tylsarová, V; Drlík, L; Strnad, M (Casopis lekaru ceskych, 2005)
The authors describe a case of 41-year-old patient with erythema nodosum as a manifestation of colitis ulcerosa. They stress the importance of complex look at this skin disease, which can be caused by many factors. Non-specific intestinal inflammation can be a cause of the erythema nodosum in 1-2%.
Keywords: Female; Erythema Nodosum; Adult; dospělí; erythema nodosum; ženské pohlaví; Humans; lidé; Colitis, Ulcerative; ulcerózní kolitida